2018
DOI: 10.3390/nu10050531
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Alleviates Hepatic Oxidative Stress and Insulin Resistance in Diabetic Female Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) affects more than 70% of patients with type 2 diabetes mellitus (T2DM) and has become one of the most common metabolic liver diseases worldwide. To date, treatments specifically targeting NAFLD do not exist. Oxidative stress and insulin resistance have been implicated in the pathogenesis of NAFLD in diabetes. Accordingly, the goal of this present study was to determine whether Ellagic acid (EA), a natural antioxidant polyphenol found in berries and nuts, mitigates hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 76 publications
(89 reference statements)
5
55
0
1
Order By: Relevance
“…However, EA treatment prior to MPTP administration significantly increased the GSH level and decreased the MDA level, again suggesting the antioxidant function of EA. In several studies, EA has been widely reported to exert free radical scavenging and potent antioxidant activity by scavenging ROS and restoring the activity of cellular antioxidant enzymes [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, EA treatment prior to MPTP administration significantly increased the GSH level and decreased the MDA level, again suggesting the antioxidant function of EA. In several studies, EA has been widely reported to exert free radical scavenging and potent antioxidant activity by scavenging ROS and restoring the activity of cellular antioxidant enzymes [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Several biological pathways have been proposed to explain the association between nut intake and NAFLD risk. Ellagic acid, a natural antioxidant polyphenol found in nuts, can suppress oxidative stress and inflammation28 and improve hepatic insulin sensitivity and lipid metabolism 29. Vitamin E and selenium in almonds and walnuts, as well as folic acid and resveratrol in pine nuts, have been reported to have beneficial effects on NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Karena enzim yang terlibat pada pencernaan pati tersusun dari protein maka diduga senyawa penol juga dapat mengganggu aktivitas enzim-enzim tersebut. Selain itu beberapa senyawa penolik bersifat sebagai antioksidan yang diduga dapat berperan penting pada pencegahan perkembangan dan komplikasi diabetes (Ghosh et al, 2018;Polce et al, 2018).…”
Section: Pendahuluanunclassified